PENGARUH PENDAPATAN DAN BEBAN USAHA TERHADAP LABA PADA PT. GUDANG GARAM, Tbk - Iin Syofia Yandra; Melifia Liantifa (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study was to determine the effect of income and operating expenses on the profit of PT. Gudang Garam, Tbk period 2013-2022. The type of data used in this study is secondary data, namely in the form of financial statements of the gudang garam company from 2011 to 2020. Based on the results of the research, income yields t count 0.489 < t table 2.365 and sig value. 0.640 > 0.05. Thus Ho is accepted, Ha is rejected, meaning that there is no positive and insignificant effect between income and profit of PT. Gudang Garam, Tbk period 2013-2022. Based on the results of the study of operating expenses on profit, the t count 1.319 < t table 2.365 and the value of sig. 0.229 . 0.05. Thus Ho is accepted, Ha is rejected, meaning that there is no and insignificant effect between operating expenses and profits of PT. Gudang Garam, Tbk period 2013-2022. And based on the results of the simultaneous study of Income and Operating Expenses, it produces a calculated f count 16.265 > f table 5.32 and the value of sig. 0.02 <0.05 this proves that Ho is rejected, Ha is accepted, meaning that there is a significant influence between Revenue and Operating Expenses on Profit PT. Gudang Garam, Tbk period 2013-2022